FSR motor control and learning lab: tracing the microscopic movements / Muhamad Noor Mohamed - Mohamed, Muhamad Noor (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Human movement is a complex phenomenon that involves the interaction of various body systems, such as the skeletal, muscular, nervous, and cardiovascular systems. Depending on the type and purpose of the movement, different patterns of coordination, control, and adaptation can be observed. Researchers have developed various models and methods to describe and analyze human movement, ranging from theory-driven to data-driven approaches. Theory-driven models incorporate anatomical and physiological aspects of movement generation, while data-driven models focus on specific aspects or outcomes of movement performance. Both types of models have advantages and limitations, depending on the research question and the available data [1]. Some examples of human movement types are flexion, extension, abduction, adduction, rotation, pronation, supination, circumduction, deviation, opposition, repositioning, inversion, and eversion.